Assessing the relationship between quality of life and marital satisfaction among Malaysian married couples - Rozmi Ismail,; Azlan H. A.N.,; Yusoff F., (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
The increase of living cost due to rapid global economic changes forced husband and wife go out to work and spent less time for families, consequently cause the decline in marital happiness and quality of life. This paper investigates factors that influence couples’marital satisfaction on their quality of life.A total of 603 married couples participated in this study by completing the ENRICH Marital Satisfaction Scale (EMS) and Quality of Life instruments. The results found that age, gender, duration of marriage, family income, number of children contributed to marital dissatisfaction and low quality of life. Multivariate analysis revealed that the increase in marital quality will lead to decrease in QOL. The implication of this study suggested that all stake holders and government agency should focus on the policy to improving quality of life and happiness.